Representasi Wajah Kota Yogyakarta dalam Wacana Meme di Media Sosial: Kajian Semiotika - Daumi Rahmatika Zuhdah (Balai Bahasa Provinsi Riau, 2023)
Memes were produced based on the creator's experience and expectation of Yogyakarta city with particular signs to reconstruct the reality of life in Yogyakarta. So, this research aims to analyze people's perception of Yogyakarta city through memes. This research uses qualitative descriptive methods with semiotics analysis of Barthes. The data was verbal and non-verbal signs from a data source of memes. The data was collected by observing and archiving Twitter memes concerning Yogyakarta city. Data analysis was conducted by grouping the top issues discussed in memes and describing them using Barthes's semiotics analysis. The results found that the memes of Yogyakarta were delivered as satire and humor with a negative tendency. According to the analysis, the portrait of Yogyakarta was laid on social issues rarely discussed and known by outsiders of Yogyakarta. The term 'istimewa' was questionable, knowing people find unpopular opinions regarding Yogyakarta city.